Phosphinocyclodextrins as confining units for catalytic metal centres. Applications to carbon–carbon bond forming reactions - Jouffroy, Matthieu; Gramage-Doria, Rafael; Sémeril, David; Armspach, Dominique; Matt, Dominique; Oberhauser, Werner; Toupet, Loïc (Beilstein Journal of Organic Chemistry, 2014)
The capacity of two cavity-shaped ligands, HUGPHOS-1 and HUGPHOS-2, to generate exclusively singly phosphorus-ligated complexes, in which the cyclodextrin cavity tightly wraps around the metal centre, was explored with a number of late transition metal cations. Both cyclodextrin-derived ligands were assessed in palladium-catalysed Mizoroki–Heck coupling reactions between aryl bromides and styrene on one hand, and the rhodium-catalysed asymmetric hydroformylation of styrene on the other hand. The inability of both chiral ligands to form standard bis(phosphine) complexes under catalytic conditions was established by high-pressure NMR studies and shown to have a deep impact on the two carbon–carbon bond forming reactions both in terms of activity and selectivity. For example, when used as ligands in the rhodium-catalysed hydroformylation of styrene, they lead to both high isoselectivity and high enantioselectivity. In the study dealing with the Mizoroki–Heck reactions, comparative tests were carried out with WIDEPHOS, a diphosphine analogue of HUGPHOS-2.
Keywords: asymmetric hydroformylation; cyclodextrin; Heck reaction; homogeneous catalysis; palladium; phosphine; rhodium

(untitled) - Littke, A. F.; Fu, G. C. (J. Org. Chem., 1999)

(untitled) - Stambuli, J. P.; Stauffer, S. R.; Shaughnessy, K. H.; Hartwig, J. F. (J. Am. Chem. Soc., 2001)

(untitled) - Littke, A. F.; Fu, G. C. (J. Am. Chem. Soc., 2001)

(untitled) - Wolfe, J. P.; Singer, R. A.; Yang, B. H.; Buchwald, S. L. (J. Am. Chem. Soc., 1999)

(untitled) - Kataoka, N.; Shelby, Q.; Stambuli, J. P.; Hartwig, J. F. (J. Org. Chem., 2002)

(untitled) - Walker, S. D.; Barder, T. E.; Martinelli, J. R.; Buchwald, S. L. (Angew. Chem., Int. Ed., 2004)

(untitled) - Ohzu, Y.; Goto, K.; Kawashima, T. (Angew. Chem., Int. Ed., 2003)

(untitled) - Iwasawa, T.; Komano, T.; Tajima, A.; Tokunaga, M.; Obora, Y.; Fujihara, T.; Tsuji, Y. (Organometallics, 2006)

(untitled) - Ohta, H.; Tokunaga, M.; Obora, Y.; Iwai, T.; Iwasawa, T.; Fujihara, T.; Tsuji, Y. (Org. Lett., 2007)

(untitled) - Dodds, D. L.; Boele, M. D. K.; van Strijdonck, G. P. F.; de Vries, J. G.; van Leeuwen, P. W. N. M.; Kamer, P. C. J. (Eur. J. Inorg. Chem., 2012)

(untitled) - Fujihara, T.; Yoshida, S.; Ohta, H.; Tsuji, Y. (Angew. Chem., Int. Ed., 2008)

(untitled) - Snelders, D. J. M.; van Koten, G.; Klein Gebbink, R. J. M. (J. Am. Chem. Soc., 2009)

(untitled) - Kwong, F. Y.; Chan, A. S. C. (Synlett, 2008)

(untitled) - Surry, D. S.; Buchwald, S. L. (Angew. Chem., Int. Ed., 2008)

(untitled) - Monnereau, L.; Sémeril, D.; Matt, D.; Toupet, L. (Chem. – Eur. J., 2010)

(untitled) - Pruett, R. L.; Smith, J. A. (J. Org. Chem., 1969)

(untitled) - Dabbawala, A. A.; Bajaj, H. C.; Jasra, R. V. (J. Mol. Catal. A, 2009)

(untitled) - Dabbawala, A. A.; Jasra, R. V.; Bajaj, H. C. (Catal. Commun., 2010)

(untitled) - Kubis, C.; Ludwig, R.; Sawall, M.; Neymeyr, K.; Börner, A.; Wiese, K.-D.; Hess, D.; Franke, R.; Selent, D. (ChemCatChem, 2010)

(untitled) - Kubis, C.; Selent, D.; Sawall, M.; Ludwig, R.; Neymeyr, K.; Baumann, W.; Franke, R.; Börner, A. (Chem. – Eur. J., 2012)

(untitled) - Tricas, H.; Diebolt, O.; van Leeuwen, P. W. N. M. (J. Catal., 2013)

Rhodium Catalyzed Hydroformylation - van Leeuwen, P. W. N. M.; Claver, C. (Kluwer Academic Publishers, 2002)

(untitled) - Selent, D.; Wiese, K.-D.; Röttger, D.; Börner, A. (Angew. Chem., Int. Ed., 2000)

(untitled) - Breit, B.; Winde, R.; Mackewitz, T.; Paciello, R.; Harms, K. (Chem. – Eur. J., 2001)

(untitled) - Baber, R. A.; Clarke, M. L.; Heslop, K. M.; Marr, A. C.; Orpen, A. G.; Pringle, P. G.; Ward, A.; Zambrano-Williams, D. E. (Dalton Trans., 2005)

(untitled) - Clarke, M. L. (Curr. Org. Chem., 2005)

(untitled) - Rafter, E.; Gilheany, D. G.; Reek, J. N. H.; van Leeuwen, P. W. N. M. (ChemCatChem, 2010)

(untitled) - Dabbawala, A. A.; Jasra, R. V.; Bajaj, H. C. (Catal. Commun., 2011)

(untitled) - Dabbawala, A. A.; Bajaj, H. C.; Rao, G. V. S.; Abdi, S. H. R. (Appl. Catal., A: Gen., 2012)

(untitled) - Bellini, R.; Reek, J. N. (Chem. – Eur. J., 2012)

(untitled) - Bellini, R.; Chikkali, S. H.; Berthon-Gelloz, G.; Reek, J. N. H. (Angew. Chem., Int. Ed., 2011)

(untitled) - Bocokić, V.; Kalkan, A.; Lutz, M.; Spek, A. L.; Gryko, D. T.; Reek, J. N. H. (Nat. Commun., 2013)

(untitled) - Agbossou, F.; Carpentier, J.-F.; Mortreux, A. (Chem. Rev., 1995)

(untitled) - Claver, C.; Diéguez, M.; Pàmies, O.; Castillón, S. (Top. Organomet. Chem., 2006)

(untitled) - Klosin, J.; Landis, C. R. (Acc. Chem. Res., 2007)

(untitled) - Gual, A.; Godard, C.; Castillón, S.; Claver, C. (Tetrahedron: Asymmetry, 2010)

(untitled) - Franke, R.; Selent, D.; Börner, A. (Chem. Rev., 2012)

(untitled) - Engeldinger, E.; Poorters, L.; Armspach, D.; Matt, D.; Toupet, L. (Chem. Commun., 2004)

(untitled) - Gramage-Doria, R.; Rodriguez-Lucena, D.; Armspach, D.; Egloff, C.; Jouffroy, M.; Matt, D.; Toupet, L. (Chem. – Eur. J., 2011)

(untitled) - Machut-Binkowski, C.; Legrand, F.-X.; Azaroual, N.; Tilloy, S.; Monflier, E. (Chem. – Eur. J., 2010)

(untitled) - Legrand, F.-X.; Six, N.; Slomianny, C.; Bricout, H.; Tilloy, S.; Monflier, E. (Adv. Synth. Catal., 2011)

(untitled) - Tran, D. N.; Legrand, F.-X.; Menuel, S.; Bricout, H.; Tilloy, S.; Monflier, E. (Chem. Commun., 2012)

(untitled) - Takashima, Y.; Uramatsu, K.; Jomori, D.; Harima, A.; Otsubo, M.; Yamaguchi, H.; Harada, A. (ACS Macro Lett., 2013)

(untitled) - Jouffroy, M.; Gramage-Doria, R.; Armspach, D.; Sémeril, D.; Oberhauser, W.; Matt, D.; Toupet, L. (Angew. Chem., Int. Ed., 2014)

Large Cavity Cyclodextrin-Based Macrocyclic Ligands: Synthesis, Coordination and Catalytic Properties - Gramage-Doria, R. (Université de Strasbourg, 2012)

(untitled) - Engeldinger, E.; Armspach, D.; Matt, D.; Jones, P. G.; Welter, R. (Angew. Chem., Int. Ed., 2002)

(untitled) - Gramage-Doria, R.; Armspach, D.; Matt, D. (Coord. Chem. Rev., 2013)

(untitled) - Kaufmann, W.; Venanzi, L. M.; Albinati, A. (Inorg. Chem., 1988)

(untitled) - Espinet, P.; Martínez-Ilarduya, J. M.; Pérez-Briso, C.; Casado, A. L.; Alonso, M. A. (J. Organomet. Chem., 1998)

(untitled) - Bartolomé, C.; Espinet, P.; Vicente, L.; Villafañe, F.; Charmant, J. P. H.; Orpen, A. G. (Organometallics, 2002)

(untitled) - Vicente, J.; Arcas, A. (Coord. Chem. Rev., 2005)

(untitled) - Gramage-Doria, R.; Armspach, D.; Matt, D.; Toupet, L. (Angew. Chem., Int. Ed., 2011)

(untitled) - Engeldinger, E.; Armspach, D.; Matt, D.; Jones, P. G. (Chem. – Eur. J., 2003)

(untitled) - Li Wu, M.; Desmond, M. J.; Drago, R. S. (Inorg. Chem., 1979)

(untitled) - Uguagliati, P.; Deganello, G.; Busetto, L.; Belluco, U. (Inorg. Chem., 1969)

(untitled) - Deganello, G.; Uguagliati, P.; Crociani, B.; Belluco, U. (J. Chem. Soc. A, 1969)

(untitled) - Wood, C. D.; Garrou, P. E. (Organometallics, 1984)

(untitled) - Leigh, J. S.; Whitmire, K. H. (Acta Crystallogr., Sect. C, 1989)

(untitled) - Bartik, T.; Krümmung, T.; Happ, B.; Sieker, A.; Markó, L.; Boese, R.; Ugo, R.; Zucchi, C.; Pályi, G. (Catal. Lett., 1993)

Inorganic Chemistry - Miessler, G. L.; Tarr, D. A. (Pearson Prentice Hall, 2011)

(untitled) - Adint, T. T.; Wong, G. W.; Landis, C. R. (J. Org. Chem., 2013)

(untitled) - Nelsen, E. R.; Landis, C. R. (J. Am. Chem. Soc., 2013)

(untitled) - Noonan, G. M.; Cobley, C. J.; Mahoney, T.; Clarke, M. L. (Chem. Commun., 2014)

(untitled) - Ziegler, C. B., Jr; Heck, R. F. (J. Org. Chem., 1978)

(untitled) - Heck, R. F.; Nolley, J. P. (J. Org. Chem., 1972)

(untitled) - Gillie, A.; Stille, J. K. (J. Am. Chem. Soc., 1980)

(untitled) - Sliger, M. D.; Broker, G. A.; Griffin, S. T.; Rogers, R. D.; Shaughnessy, K. H. (J. Organomet. Chem., 2005)

(untitled) - Gramage-Doria, R.; Armspach, D.; Matt, D.; Toupet, L. (Chem. – Eur. J., 2012)

(untitled) - Sémeril, D.; Lejeune, M.; Jeunesse, C.; Matt, D. (J. Mol. Catal. A, 2005)

(untitled) - El Moll, H.; Sémeril, D.; Matt, D.; Youinou, M.-T.; Toupet, L. (Org. Biomol. Chem., 2009)

(untitled) - Shaughnessy, K. H.; Kim, P.; Hartwig, J. F. (J. Am. Chem. Soc., 1999)

(untitled) - Kanagaraj, K.; Pitchumani, K. (Chem. – Eur. J., 2013)

(untitled) - Ben-David, Y.; Portnoy, M.; Gozin, M.; Milstein, D. (Organometallics, 1992)

(untitled) - Crisp, G. T. (Chem. Soc. Rev., 1998)

(untitled) - Beletskaya, I. P.; Cheprakov, A. V. (Chem. Rev., 2000)

(untitled) - Whitcombe, N. J.; Hii, K. K.; Gibson, S. E. (Tetrahedron, 2001)

(untitled) - Surawatanawong, P.; Fan, Y.; Hall, M. B. (J. Organomet. Chem., 2008)

(untitled) - Amatore, C.; Jutand, A. (Acc. Chem. Res., 2000)

(untitled) - Knowles, J. P.; Whiting, A. (Org. Biomol. Chem., 2007)

Mechanisms of the Mizoroki–Heck Reaction - Jutand, A. (John Wiley & Sons, Ltd., 2009)

(untitled) - Sumimoto, M.; Kuroda, T.; Yokogawa, D.; Yamamoto, H.; Hori, K. (J. Organomet. Chem., 2012)

(untitled) - van Strijdonck, G. P. F.; Boele, M. D. K.; Kamer, P. C. J.; de Vries, J. G.; van Leeuwen, P. W. N. M. (Eur. J. Inorg. Chem., 1999)

(untitled) - Engeldinger, E.; Armspach, D.; Matt, D. (Angew. Chem., Int. Ed., 2001)

(untitled) - Wong, Y. T.; Yang, C.; Ying, K.-C.; Jia, G. (Organometallics, 2002)

(untitled) - Schlatter, A.; Kundu, M. K.; Woggon, W.-D. (Angew. Chem., Int. Ed., 2004)

(untitled) - Liu, K.; Häussinger, D.; Woggon, W.-D. (Synlett, 2007)

(untitled) - Schlatter, A.; Woggon, W.-D. (Adv. Synth. Catal., 2008)

(untitled) - Guitet, M.; Zhang, P.; Marcelo, F.; Tugny, C.; Jiménez-Barbero, J.; Buriez, O.; Amatore, C.; Mouriès-Mansuy, V.; Goddard, J.-P.; Fensterbank, L.; Zhang, Y.; Roland, S.; et al. (Angew. Chem., Int. Ed., 2013)

The Chemistry of Platinum and Palladium - Hartley, F. R. (Wiley, 1973)